STATIC AND DYNAMIC MAPS, DEVELOPED FROM AN ANALYTICAL OR SYNTHESIS REASONING, IN SCHOOL GEOGRAPHIC ATLAS: THE METHODOLOGICAL FEASIBILITY - Martinelli, Marcello; Machado-Hess, Elizabeth de Souza (Revista Brasileira de Cartografia, 2014)
On the teaching and learning of Geography, at least in Europe, School Geographic Atlases have earned credit among the didactic materials since the early nineteenth century. The fi rst school atlas of the european continent was the germanic Â«Kleiner Atlas ScholasticusÂ», concluded in 1710. Other similar atlases appeared, conceived as simplifi cations of the great General Reference Atlases. The Â«Atlas Général Vidal-Lablache: histoire et géographieÂ» (1894) was a classic that inspired other derivations. The fi rst Brazilian School Atlas was the Atlas of the Empire of Brazil, by Cândido Mendes de Almeida, published in 1868. As a result of the evolution of cartography, a wide range of School atlases, not only global but also national, regional, state, provincial and even local atlases, are currently available in print, digital and electronic media. In order to develop a School Geographic Atlas, the initial step is the interlace of two basic guidelines in which space and time are present: fi rst, the teaching the map, considering the theoretical and methodological bases about the construction and representation of space in the child. This representation process in the child starts with its own spatial reality and later, it continues with the reality of other people; second, the teaching with the map, practiced in Geography to achieve the knowledge of the world, from the close and known experience (the place) to the distant unknown (the world space), not linearly, but going back and forth through the various levels of approach. Thus, there will be the understanding how the local reality has a strong relationship with the rest of the world. The student will be able to think on a particular context without having experienced it before. The next step deals with the defi nition of the Atlas contents and the delimitation of the spatial area, taking into account the methodological basis of the Geography. In addition, the Thematic Cartography can be considered as a monosemic language. As a consequence, the thematic maps can be constructed by applying various methods, with their own level of adequacy to represent the selected theme, in a static or dynamic appreciation. Moreover, the reality can be glimpsed inside an analytical or synthesis reasoning. Within the previous outlook, this speculation will give emphasis to the participation of maps, as the integral elements of school geographic atlas, constructed in accordance with a static or dynamic appreciation, developed following two distinct levels of reasoning, either analytical or even synthesis.